THE INSTITUTION OF URBARARS IN MEDIAEVAL SERBIA (Heritage, 2020)
Bohemia and Serbia. The aim of this paper is to compare Serbian and Bohemian mediaeval solutions and to discover whether and to what degree urbarars were an original development within the Serbian mediaeval state.                             The results show that the two institutions are similar with regard to their judicial competence and the task of keeping registries of legal titles. The differences are more numerous. Bohemian urbarars were at the same time contractors for regal incomes, which leads to further differences. Serbian urbarars had smaller competences and, according to the sources, did not collect the urbor. Their jurisdiction was much narrower, confined to mining disputes of lower value. They survey the mining field and keep records about concessions and mining partnerships, which, in Bohemia, was the task of special notaries and not urbarars. The urbarars of Novo Brdo received compensation for their services in the form of fees for surveys and registration of legal titles, as well as fines for delicts, while Bohemian urbarars received a part of the collected regal income.                Taking everything into account, it can be cautiously concluded that Bohemian solutions were closer to Saxon customs. On the one hand, Bohemian legal sources are at least a century older than the Serbian sources, on the other hand, Saxons in Serbia were few and were quickly assimilated, whereas Germans remained a significant community in Bohemia well into the XX century, which means that they could preserve their customs, as well as legal customs, more easily. This confirms the authenticity of a good part of norms of Serbian mining law, i.e. that from XIII to XV century it experienced a sui generis development in Serbia. It was then received in the Ottoman Empire and survived the state which created it by several centuries.                The applied methods are linguistic, systemic and historical interpretation of the sources, as well as the comparative and historical method.
Keywords: urbarars, mining law, Serbian law, medieval law, Bergregal